The Doctrine of Exemplarism: A Symbolic Attempt to Escape the Pelagian Heresy - Gordon, Liran Shia (Religions, 2023)
Heresies are intrinsically intertwined with the evolution and inner growth of the very religions that denounce them. They serve as theological junctures, challenging and thus refining the orthodoxy of religious beliefs. The Pelagian heresy touches on one of the central tenets of Christian theology: the question of salvation. Pelagianism posits that human beings retain freedom of the will and, more specifically, the capacity to earn salvation through their own merits rather than relying solely on the grace of God in Christ. This stands in contrast to the predominant Christian view that Original Sin fundamentally impaired man’s will and intellect. A central tenet of Christianity is that through His suffering and death on the Cross, Christ atoned for humanity’s Original Sin and paved the way for our redemption. But what exactly made this redemption possible through the suffering and death on the Cross? Unlike many of the answers offered, Abelard’s explanation, also referred to as exemplarism, resonates with modern sensibilities: Christ set an example to imitate, and through this imitation, man learns humility and love. However, this stance faced criticism and was condemned by Bernard of Clairvaux as having Pelagian tendencies because it suggests that Christ’s redemptive work might not inherently require Christ’s divine nature. This study will attempt to defend the exemplaristic approach while ensuring Christ’s essential role and addressing criticisms against the Pelagian heresy. This discussion is further enriched by an examination of the Eucharist, illuminating the theological tension between symbolic and realistic interpretations of religious rites.